Demystifying switching power supplies - Mack, Raymond A.
This book is a crash course in the fundamental theory, concepts, and terminology of switching power supplies. It is designed to quickly prepare engineers to make key decisions about power supplies for their projects. Intended for readers who need to quickly understand the key points of switching power supplies, this book covers the 20% of the topic that engineers use, 80% of the time. Unlike existing switching power supply books that deal strictly with design issues, this book also recognizes the growing importance of "off-the-shelf" commercial switching power supplies, giving readers the back.